2015
DOI: 10.1177/0009922815587090
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing Care Gaps for Early Language Delay

Abstract: Background and Objective Poverty is a risk factor for both language delay and failure to access appropriate therapies. The objective of this study was to increase the percentage of children 0 to 3 years old referred from an urban primary care center who attended an initial appointment with speech pathology or audiology within 60 days from 40% to 60%. Methods The Model for Improvement was used to develop and test the intervention, which addressed potential logistical barriers faced by low-income families. Adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…It stills the low percentage of cases from rural areas may indicate a lack of education and or availability of services. Brown et al Stated that poverty, lack of acknowledge, is a risk factor for both language delay and failure to access appropriate therapies [27] . Thus, more attention should direct for the rural areas with respect to the services and planning to raise awareness about DLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It stills the low percentage of cases from rural areas may indicate a lack of education and or availability of services. Brown et al Stated that poverty, lack of acknowledge, is a risk factor for both language delay and failure to access appropriate therapies [27] . Thus, more attention should direct for the rural areas with respect to the services and planning to raise awareness about DLD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, sever and profound ID was of 17.1 % (47 cases out of a total of 275 children presented in a year with ID). Actually, severe and profound levels have a higher risk of developing health problems and medical complications, and most of them need pharmacological treatments for long term [26][27] , as well as a high prevalence of them are severely limited in their ability to understand or comply with requests or instructions, and require intensive constant training and support in various life aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, cerca de la mitad de los participantes con retraso del lenguaje no completaron las evaluaciones de fase 2, lo que evidenció dificultades de accesibilidad y adherencia que también se observaron en otros países. 35 Entre las principales fortalezas de este trabajo, se resaltan la base poblacional en el primer nivel de atención, el abordaje multidimensional según el modelo ecológico con instrumentos equivalentes a los utilizados en la bibliografía internacional y, en su mayoría, validados localmente, como también la caracterización de los niños y niñas con retraso del lenguaje respecto del compromiso receptivo y posibles causas subyacentes.…”
Section: Discussionunclassified
“…However, financial barriers are still significant, and many studies have shown that children from lowincome families are less likely to receive speech pathology support (118,125).…”
Section: Financial Barriersmentioning
confidence: 99%
“…Service access may be affected by poor understanding of the health care system (120) and referral processes (125), and cultural differences may mean that some families do not consider communication impairment to be a problem (120).…”
Section: Cognitive Barriersmentioning
confidence: 99%